NOD-like receptors in fish: evolution, structure, immune signaling, and targeting for aquaculture vaccine adjuvants - Swain, Banikalyan; Miryala, Kavi R. (Frontiers in Immunology, 2025)
Teleost fish possess a highly diverse innate immune system, which is well-adapted to the pathogen-rich aquatic environment in which they reside. NOD-like receptors (NLRs), a conserved family of cytosolic pattern recognition receptors, are at the center of this defense mechanism, activating immune responses, recognizing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Here, we present an integrative overview of the current state of fish NLRs in terms of their evolutionary diversification, structural framework, signaling pathways, and functional roles in the context of bacterial, viral, and parasitic pathogens. We discuss six principal NLRs: nucleotide-binding oligomerization domain-containing protein 1 (NOD1), NOD2, NLRC3, NLRC5, NLR family member X1 (NLRX1), and NLR family pyrin domain-containing 1 (NLRP1), highlighting their domain structures, 3D conformations, and downstream signal chains. We focused on the immune regulatory roles of NLR family acidic transactivation domain-containing (NLRA) and NLR family CARD domain-containing (NLRC) subfamily components, the formation of the NLRP1 inflammasome, and the new roles of mitochondrial-specific NLRs in antiviral immunity. We discuss future directions for NLRs as immunological targets in aquaculture, referencing known NLR-activating adjuvants, exploring their ligand specificity, and highlighting challenges like functional redundancy. Much of the insight into the fish NLRs in this review comes from their well-researched mammalian counterparts. NLR-based immune modulation represents the ability of these receptors to detect microbial or danger signals and regulate key signaling pathways, such as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), activator protein 1 (AP-1), interferon regulatory factors (IRFs), and inflammasome activation. These pathways help shape the immune response by negatively or positively altering cytokine production and improving antigen presentation. By bringing together what we know about NLR evolution, structure, and function, this review aims to support new ideas and research into how fish defend themselves from disease and how we might strengthen that defense through improved vaccine and adjuvant design.